Efeitos do carvão vegetal no solo e sobre cultivos de feijão-caupi em ambiente protegido - Melo, Isabel Giovanna Costa e (2016)
The increase in world population has led to increased demand for water and food, causing thereby greater pressure on agricultural land, and therefore its degradation and scarcity. The use of biochar in agriculture emerges as a sustainable technique, which contribution to the improvement of soil quality and crop productivity has already been highlighted in several studies. Therefore, two experiments were conducted in order to evaluate the influence of biochar application on soil chemical and physical properties and on the yield of two successive crops of cowpea. The trials were conducted in pots, in the period from March 2013 to March 2014, in a greenhouse at UFERSA, Mossoro, RN, Brazil. The experimental design was that of randomized blocks in a 4x5 factorial scheme, being tested four biochar doses (0, 3.5, 7 and 10.5 t ha-1) and five types of soil [Argisol (AS), Cambisol (CS), Oxisol (LS), Fluvic (NFS) and Quartzipsamment (NQS)] with five replications. Biochar was produced from wood resulting from the pruning of cashew trees. Variables analyzed were soil physical properties (water holding capacity and soil density), soil chemical properties [pH, soil organic matter (SOM), P, K, Na, Ca, Mg, exchangeable sodium percentage (ESP) and sum of bases (SB)], characteristics of initial growth of the seedlings (emergence percentage, seedling height and shoot dry mass per seedling) and yield components of cowpea (number of grains per pod (NGP), average length of pods (LP), hundred grain weight (HGW) and grain yield (GY)). Data were submitted to analysis of variance, besides analysis of regression or Tukey test, depending of the effects being considered. With few exceptions, the behavior of the variables was different according to the soil type. Addition of biochar provided a linear increase of 14% in the water holding capacity for the higher dose in relation to the control. Reduction in soil density was provided by biochar application only in the CS and LS. Biochar doses provided in the CS the largest linear increases in values of variables of initial growth of cowpea. Regardless of biochar dose, the NFS soil showed larger values of NGP, LP, HGW and GY of cowpea in both crops. Biochar doses provided linear increases in values of the components of yield of cowpea in both crops, with few negative effects in the second crop. Regardless of biochar dose, the largest values of P, Na, K, Ca, Mg e SB were obtained in the NFS; of pH and Na in the AS and of SOM in the CS, while NQS showed the lowest values of SOM, P, K, Na, and the largest values of ESP. Biochar doses of exerted a positive effect only on pH, SOM, P and ESP, mainly in the soils NFS and CS, however, generally, the doses did not presented consistent effects on chemical characteristics like K, Na, Ca and SB, in most soils. Negative effects of the increase in biochar dose were observed for SB, P, Na, Ca, pH, ESP, Na and K in the soils NFS, LS and CS